Comparative study of toxicological effects of lindane and isoproturon pesticides in the Saccharomyces cerevisiae - Candeias, M (2016)
Organochlorine insecticides and phenylurea herbicides such as lindane (hexachlorocyclo-hexane, γ-HCH) and isoproturon (3-(4-isopropylphenyl)-1,1-dimethylurea, IPU), used in agricultural applications for the pest and broad-leaved control, are often found in contaminated groundwater and surface water. Unfortunately, the toxicity of these pesticides in eukaryotic cells is still poorly understood. Saccharomyces cerevisiae is a promising eukaryotic organism for the toxicological evaluation of pollutants, because its metabolism is similar to that of high-level organisms. Thus the aim of this study was to compare the effects of two pesticides on yeast-cell viability and its antioxidant power. S. cerevisiae UE-ME3, a wild-type strain belonging to Oenology Laboratory of the University of Évora, grown in the presence of 50 μM γ-HCH and 100 μM IPU in 2% glucose and peptone deprivation medium (YED), at 28 °C were compared with control cells. CFU were determined at the end of the experiment and remaining cells disintegrated in 10 mM phosphate buffer pH 7.0 by sonication. Post-12,000 × g supernatant was used for determination of glutathione (GSH), glutathione disulphide (GSSG) and malondialdehyde (MDA) content and glutathione reductase (GR), glutathione peroxidase (GPx) and cytoplasmic catalase (CTT1) activity. The results showed that 50 μM γ-HCH exposures, in YED medium, did not affect cell viability, CTT1 activity, non-protein thiols (GSH + GSSG) and MDA content of S. cerevisiae. However, the 50 μM γ-HCH exposure caused a decrease in GSH/GSSG ratio, GR and GPx activity. In contrast, 100 μM IPU exposures caused an increase in the cell viability, (GSH + GSSG), GSH/GSSG ratio and GR activity. Additionally, there was a decrease in the MDA levels, GPx and CTT1 activity, under the same growth conditions. In conclusion, the presence of lindane, in YED medium, caused a reducing-oxidizing transition, a slowdown of the glutathione redox cycle without disturbing the survival of S. cerevisiae. However, the increase in the cell viability, the redox buffer power and the lipid peroxidation attenuation caused by IPU in nitrogen deprivation, appears to be due to the high regeneration capacity of GSH via GR activity, pointing out a possible use of isoproturon as nitrogen source.